PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI SWALAYAN JODOH CENTER BATAM - Mayzura, Dyla; Raymond, Raymond (LPPM Universitas Putera Batam, 2019)
More modern market make it easy for consumers for fulfil his life needs. Swalayan is a form of modern market that are much in demand by consumers. The purpose of this study was to determine the effect of price and place on purchasing decisions. Where independent variables are price and place, influence purchasing decisions as the dependent variable. The population used in this study is the consumer of Swalayan Jodoh Center Batam, with a sample of 100 respondents used as consumers of Swalayan Jodoh Center Batam. The sampling method uses purposive sampling methods and data collection techniques using questionnaires. This type of research is quantitative research. Quantitative analysis includes validity, reliability, classical assumption test, multiple linear analysis, determination coefficient (R2), f test and t test. The data from this study were processed using SPSS version 20.0. The results of this study are price has a negative and not significant influence on purchasing decisions, place has a positive and significant effect on purchasing decisions. While simultaneous results, price and place have a significant influence on Swalayan Jodoh Center Batam purchasing decisions.